Screening By Magnetic Resonance Imaging May Be Performed Even In Patients With Mild-Moderate Hyperprolactinemia - Bozdağ, Gürkan; Özyüncü, Özgür; Kart, Cavit; Esinler, İbrahim; Karakoç Sökmensüer, Lale; Aksu, Tarık; Günalp, Serdar (Gynecology Obstetrics & Reproductive Medicine, 2007)
OBJECTIVE: To evaluate the association between the degree of hyperprolactinemia and the possibility of presenting a pituitary adenoma with magnetic resonance imaging. In addition, a threshold value for prolactin level was studied in order to predict micro/macroadenoma. STUDY DESIGN: A total of 43 patients from a tertiary center, with persistent hyperprolactinemia were retrospectively evaluated. Only patients with a prolactin level more than 20ng/mL with two consecutive analyses were undertaken. Magnetic resonance imaging (MRI) was performed to all cases. RESULTS: Of the 43 cases, microadenoma and macroadenoma was observed in 14 (32.6%) and 1 (%2.3) patient, respectively. The mean levels of PRL among patients with normal pituary imaging and microadenomas were similar. The unique case with macroadenoma had a PRL level of 56.2ng/mL. When the patients (n=39) were enrolled according to PRL levels, such as <100 ng/mL (n=33) or ≥100 ng/mL (n=6), the possibility of carrying a microadenoma was found to be 33.3% and 50%, respectively (p>0.5). CONCLUSION: There is no consensus for the cut-off PRL level to predict micro/macroadenoma in patients with persistent hyperprolactinemia. According to limited data, micro/macroadenoma may be presented even in PRL levels less than 100ng/ml. Therefore, the possibility of micro/macroadenoma should not be underestimated in patients with mild-moderate hyperprolactinemia according to the available literature.